Temporal association between invasive procedures and infective endocarditis. Issue 3 (22nd September 2022) - Thornhill, Martin H; Crum, Annabel; Campbell, Richard; Stone, Tony; Lee, Ellen C; Bradburn, Mike; Fibisan, Veronica; Dayer, Mark; Prendergast, Bernard D; Lockhart, Peter; Baddour, Larry; Nicoll, Jon
Abstract : Objective: Antibiotic prophylaxis has been recommended for patients at increased risk of infective endocarditis (IE) undergoing specific invasive procedures (IPs) despite a lack of data supporting its use. Therefore, antibiotic prophylaxis recommendations ceased in the mid-2000s for all but those at high IE risk undergoing invasive dental procedures. We aimed to quantify any association between IPs and IE. Methods: All 14 731 IE hospital admissions in England between April 2010 and March 2016 were identified from national admissions data, and medical records were searched for IP performed during the 15-month period before IE admission. We compared the incidence of IP during the 3 months immediately before IE admission (case period) with the incidence during the preceding 12 months (control period) to determine whether the odds of developing IE were increased in the 3 months after certain IP. Results: The odds of IE were increased following permanent pacemaker and defibrillator implantation (OR 1.54, 95% CI 1.27 to 1.85, p<0.001), extractions/surgical tooth removal (OR 2.14, 95% CI 1.22 to 3.76, p=0.047), upper (OR 1.58, 95% CI 1.34 to 1.85, p<0.001) and lower gastrointestinal endoscopy (OR 1.66, 95% CI 1.35 to 2.04, p<0.001) and bone marrow biopsy (OR 1.76, 95% CI 1.16 to 2.69, p=0.039). Using an alternative analysis, bronchoscopy (OR 1.33, 95% CI 1.06 to 1.68, p=0.049) and blood transfusions/red cell/plasma exchange (OR 1.2, 95% CI 1.07 to 1.35, p=0.012) were also associated with IE. Conclusions: This study identifies a significant association between specific IPs (permanent pacemaker and defibrillator implantation, dental extraction, gastrointestinal endoscopy and bronchoscopy) and subsequent IE that warrants re-evaluation of current antibiotic prophylaxis recommendations to prevent IE in high IE risk individuals.